Delay-Induced Transient Oscillations in a Two-Neuron Network (Resenhas do Instituto de Matemática e Estatística da Universidade de São Paulo, 2014)
Finite transmission times between neurons, referred to as delays, may appear in hardware implementation of neural networks. We analyze the dynamics of a two-neuron network in which the delay modifies the transient and not the long-term behavior of the network. We show that the delay causes some trajectories to oscillate transiently before reaching stationary behavior and the duration of these transients increases exponentially with the delay. Such a phenomeno deteriorates network performance.